METHODS FOR DETERMINING CONTAMINATION POSSIBILITY BY TYPE II CYTOLETHAL DISTENDING TOXIN-PRODUCING BACTERIA - YAMAZAKI SHINJI; AWASTHI SHARDA PRASAD (2024)
To provide efficient detection of bacteria producing type II cytolethal distending toxin.SOLUTION: Disclosed is a method for determining contamination possibility by Escherichia albertii, a type II cytolethal distending toxin-producing bacterium, which comprises a step of contacting a subject sample or DNA extracted from the sample with a primer set so as to amplify a target gene fragment in the sample, where the preferred primer set comprises a primer having a base sequence represented by one of SEQ ID Nos: 48-58 and a primer having a base sequence represented by one of SEQ ID Nos: 59-67.SELECTED DRAWING: Figure 1 【課題】II型細胞膨化致死毒素産生菌を効率良く検出する。【解決手段】II型細胞膨化致死毒素産生菌であるエシェリキア・アルバーティによる汚染可能性を判定する方法であって、判定対象である試料又は当該試料から抽出したＤＮＡと接触させて当該試料中の対象遺伝子断片を増幅させる工程を有し、当該対象遺伝子断片を増幅させる工程において、好ましくは、配列番号４８～５８で示される塩基配列を有するプライマーの何れかと、配列番号５９～６７で示される塩基配列を有するプライマーの何れかからなるプライマーセットを用いる。【選択図】図１